Mixed numerical‐experimental method for generation of energy‐life fatigue master curves. Issue 3 (21st February 2019) - Branco, Ricardo; Prates, Pedro; Berto, Filippo; Costa, José; Antunes, Fernando
Abstract: Advanced high‐strength steels are outstanding materials to meet the current demands of automotive industry, including the reduction of vehicle weight. These high value‐added products, which operate generally under adverse service conditions, are highly susceptible to fatigue failure. Modern fatigue design approaches, namely, those based on the strain energy density concept, require detailed information about the energy‐life relationship. This paper proposes a straightforward methodology to generate energy‐life fatigue master curves on the basis of only two uniaxial low‐cycle fatigue tests and two elastic‐plastic finite‐element models. The methodology is successfully tested in an advanced high‐strength steel.